Scientific research in medical education - Monge, Carlos (1956)
In the opening ceremony of the scientific proceedings of the Centennial of the Faculty and a tribute to its founder Cayetano Heredia, wanted Dean Lord grant me the honor of being the spokesman of the scientific and educational thought of the School.